FUTURES LITERACY: CONNECTIONS BETWEEN DIGITALITY AND SUSTAINABILITY IN EDUCATIONAL CONTEXTS - Gerhard Brandhofer (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Futures Literacy is defined as the ability to imagine, understand, and prepare for possible futures, empowering individuals and organizations to act proactively in the present, specifically aiming at shaping preferable futures. This competence is regarded as one of the key qualifications of the 21st century, fostering both individual agency in managing uncertainty and collective engagement for societal transformation. This contribution explores the connection between Futures Literacy and education within a culture of Digitality, particularly against the backdrop of the VUCA world (Volatility, Uncertainty, Complexity, Ambiguity). The transformation towards a transformative education is essential to equip learners for the challenges of rapid technological change and complex societal demands. The integration of Digitality and Futures Literacy necessitates a systematic anchoring in teacher education, a critical digital professionalization, and a shift towards a participatory and collaborative teaching culture. Future research should focus on the epistemological foundations, empirical application in digital contexts, and the ethical implications of technological components like Artificial Intelligence and Big Data in anticipation processes. The overarching goal of futures education is to question and disrupt the way we anticipate the future, making the verification of paradigms a key strategy for overcoming the crises of the Anthropocene.